Analysis of Factors Affecting Online Shopping Activities for MSME Products During the COVID-19 Pandemic - Himawan, Erry Nugroho; Pasaribu, Popy Novita (prodima@fe.uika-bogor.ac.id, 2024)
The Covid19 pandemic has become a game-changer for human life, including shopping procedures and habits. During this pandemic, there was an increase in online shopping activities, including shopping for MSME products. In this study, an analysis of the factors that influence online shopping activities for MSME products was carried out in the Bogor area and its surroundings. Data was collected through online questionnaires distributed by snowballing. From the results of data processing, 3 variables that significantly influence are Hedonic Motivation, Internal Subject Norm, and Behavioral Intention. For further research, it is recommended to add variable testing of the quality of goods/products, quality of shop/merchant services, satisfaction with services/products, the reputation of merchants, and a sense of security for online transactions in the marketplace.